2016
DOI: 10.1590/1516-635x1801023-028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Direct and Enrichment Iso 10272 Methods for the Detection of Campylobacter Spp. in Chicken Meat

Abstract: In 2006, the International Organization for Standardization (ISO) published two standard protocols for the detection and enumeration of Campylobacter spp. in foods: the ISO 10272-2(direct method) and the ISO 10272-1 (enrichment method). The aim of this study was to compare the efficiency of these two methods in the detection of Campylobacter spp. and propose a modification in the enrichment method. Compared with the enrichment method, the direct method yielded a higher number of positive results for Campylobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Furthermore, due to the difficulty of isolating these bacteria in addition to their nutritional and environmental requirements (3), a lot of studies indicate that false-negative results have been observed during the detection of Campylobacter spp. in food, notably in poultry meat (3,4) and human fecal specimens with rates ranging from 24% to 40% (5,6). These alarming observations indicate that the use of appropriate enrichment broths, selective agar media, and specific conditions that allow regular growth are important for the recovery of C. spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, due to the difficulty of isolating these bacteria in addition to their nutritional and environmental requirements (3), a lot of studies indicate that false-negative results have been observed during the detection of Campylobacter spp. in food, notably in poultry meat (3,4) and human fecal specimens with rates ranging from 24% to 40% (5,6). These alarming observations indicate that the use of appropriate enrichment broths, selective agar media, and specific conditions that allow regular growth are important for the recovery of C. spp.…”
Section: Introductionmentioning
confidence: 99%
“…These alarming observations indicate that the use of appropriate enrichment broths, selective agar media, and specific conditions that allow regular growth are important for the recovery of C. spp. from poultry meat (3,4) and other types of samples.…”
Section: Introductionmentioning
confidence: 99%